A country-based data analysis of risk factors for cercival cancer in Colombia (2017)
"Cervical cancer in one of the most common cancer worldwide. There are several screening policies that aim to reduce the incidence, prevalence and mortality rate, that consider some of the global risk factors but leave out some of the country specific factors that rise the risk of having the disease. For improving the screening policies, we developed a multilevel regression logistic model, taking as groups the department of living, and compare the risk factors of 2 surveys taken in 2010 and 2015 to Colombian population, for detecting the risk factors of the incidence of the disease in Colombia. Factors as living in violent environments and having previous STD should be considered in the cervical cancer screening policies for improving the life quality of Colombian women". -- Tomado del Formato de Documento de Grado.